2013
DOI: 10.1097/mpg.0b013e318282aa12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fecal Microbiota of Children With Diarrhea in 2 Locations in Colombia

Abstract: Our results suggested that changes in fecal microbiota composition of children with clinical diarrhea are associated with certain demographic factors that should be considered before designing a prophylactic intervention. Delivery of certain Lactobacillus species and Bifidobacterium species or a diet rich in bifidogenic components that promote growth of Bifidobacterium species could provide a prophylactic effect to ameliorate the effect of diarrhea in children at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 53 publications
1
23
0
1
Order By: Relevance
“…21 Our results are also in agreement with previously described ex vivo studies with whole blood cells 14 or enriched cell populations where dendritic cells exposed to different Bifidobacterium ssp were also able to upregulate the expression of HLA-DR and the co-stimulatory molecules CD86 and CD80, which can help trigger antigen specific T-cell responses indicating a higher immune stimulating ability. 25,30 In this study, we wanted to determine the potency of B. lactis to regulate the co-stimulatory molecules CD80, CD86, CD40 and HLA-DR, which are required for an effective activation of T-cells. B. lactis induced upregulation of CD40 and CD80 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Our results are also in agreement with previously described ex vivo studies with whole blood cells 14 or enriched cell populations where dendritic cells exposed to different Bifidobacterium ssp were also able to upregulate the expression of HLA-DR and the co-stimulatory molecules CD86 and CD80, which can help trigger antigen specific T-cell responses indicating a higher immune stimulating ability. 25,30 In this study, we wanted to determine the potency of B. lactis to regulate the co-stimulatory molecules CD80, CD86, CD40 and HLA-DR, which are required for an effective activation of T-cells. B. lactis induced upregulation of CD40 and CD80 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest detection limit of all assays was between 10-100 copies of specific bacterial gene copy per reaction. 30 All molecular assays were performed in the 7700-ABI PRISM (PerkinElmer, Waltham, MA) using a 25 uL PCR amplification mixture containing 1X Thermo-start QPCR master mix with ROX (Abgene, Rochester, NY), forward, reverse, probe and an equivalent of 20 ng of DNA. The amplification conditions were 50 C for 2 minutes, 95 C for 10 minutes, and 40 cycles at 95 C for 15 seconds, and 60 C for 1 minute.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…2,6,8 Diarrhea episodes have been shown to be associated with an overall decrease in phylogenetic diversity. [9][10][11][12] Although modifications in the relative abundance of taxa differ by study site, studies have shown increases in the relative abundance of the phylum Proteobacteria and decreases in Bifidobacterium and Lactobacillus during diarrhea episodes. [10][11][12] These alterations in the gut microbiota during diarrhea episodes in the early years of life may have a substantial impact on the subsequent development of the gut microbiota and its related functions.…”
Section: 3mentioning
confidence: 99%
“…[9][10][11][12] Although modifications in the relative abundance of taxa differ by study site, studies have shown increases in the relative abundance of the phylum Proteobacteria and decreases in Bifidobacterium and Lactobacillus during diarrhea episodes. [10][11][12] These alterations in the gut microbiota during diarrhea episodes in the early years of life may have a substantial impact on the subsequent development of the gut microbiota and its related functions. These effects may be especially important in developing world settings, where children commonly experience several diarrhea episodes per year.…”
Section: 3mentioning
confidence: 99%
“…Therefore, NV has been considered the most important cause of epidemic gastroenteritis, the second most important cause of endemic gastroenteritis in all age groups worldwide and a common cause of sporadic nonbacterial gastroenteritis in individuals of all ages. The overall clinical burden caused by NV infection is thought to be milder than the one given by RV (Beersma et al 2009, Yanga et al 2010 because RV infections are known to be more severe and more often associated with a complicated course (Donaldson et al 2008, Ciarlet & Schödel 2009, Lin et al 2010, Meraabi et al 2011, Rivera et al 2011, Wiegering et al 2011, Solano-Aguilar et al 2012 One of the main reasons of the important prevalence of those viruses is their route of infection. The fecal-oral route is the common route of transmission, typically through food, water or contaminated surfaces; but person-to-person transmission, by direct contact or exposure to aerosols from vomit, are also important (Wilhelmi et al 2003, Wu et al 2008, Ribes & Buesa 2010, Wiegering et al 2011, Lopman et al 2012.…”
Section: Introductionmentioning
confidence: 99%